2015
DOI: 10.1902/jop.2014.140333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Osteogenic Potential of Growth Factor–Rich Demineralized Bone Matrix In Vivo

Abstract: GDBM demonstrated acceptable biocompatibility and osteogenic potential comparable to ABBM in vivo. Further investigations in a more clinically relevant model are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, in bone decellularization protocols, partial decalcification is often applied, mainly for handling purposes, but also for improving osteoinductive properties. Urist et al [ 32 ] showed decades ago that the decalcification of native bone is able to not only retain bone morphogenic proteins and growth factors entrapped in the bone matrix, but even to further expose them and therefore facilitate specific cell–ECM interactions [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in bone decellularization protocols, partial decalcification is often applied, mainly for handling purposes, but also for improving osteoinductive properties. Urist et al [ 32 ] showed decades ago that the decalcification of native bone is able to not only retain bone morphogenic proteins and growth factors entrapped in the bone matrix, but even to further expose them and therefore facilitate specific cell–ECM interactions [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…DBM has excellent biological properties, osteoinductive, osteoconductive, biodegradability, promotes bone mineralization, and accelerates bone healing [46]. As an allograft bone graft, the natural advantages (Table 1) of decalcified bone are as follows: (1) Decalcification removes the dense mineral components which wrap around BMPs and other growth factors, consequently these factors can be released smoothly and exerts osteogenic activity [47,48]; (2) DBM is one of the weakest immunogens in alternative bone graft materials after being treated with various chemical agents; (3) DBM has the natural bone composition, reticular pore structure and 3D structure. It also has good affinity and binding force, so it can be used as a natural carrier of a variety of growth factors, which was conducive to seed cell adhesion and growth.…”
Section: Natural Bone Graftmentioning
confidence: 99%
“…Actually, the organic components of DBMs mainly consist of two parts: collagen protein and noncollagenous proteins. These noncollagenous proteins undertake almost all biological functions of DBMs, including osteoinductivity, which offers a considerable advantage to DBMs with respect to bone reconstruction . Bone morphogenetic protein 2 (BMP‐2), as one of these noncollagenous proteins in DBMs, is believed to promote the osteogenic differentiation of stem cells and formation of new bone .…”
Section: Introductionmentioning
confidence: 99%
“…These noncollagenous proteins undertake almost all biological functions of DBMs, including osteoinductivity, which offers a considerable advantage to DBMs with respect to bone reconstruction. 10,11 Bone morphogenetic protein 2 (BMP-2), as one of these noncollagenous proteins in DBMs, is believed to promote the osteogenic differentiation of stem cells and formation of new bone. [12][13][14][15] Moreover, BMP-2 is the only common link between the various forms of heterotopic ossification (HO).…”
Section: Introductionmentioning
confidence: 99%